Entre o protestantismo e os cultos afro-brasileiros: especificidades do sincretismo das igrejas neopentecostais - Oliveira Júnior, Humberto Ramos de (2013)
This study was intended to analyse the characteristic syncretism of the neo-pentecostal evangelical churches by addressing their specificities and some consequences to the Brazilian religious filed. In this work it was chosen to emphasize the relationship of neo-pentecostal syncretism with Brazilian culture and also with the religions of African origin. The main hypothesis is the Neo-pentecostalism, due to its syncretic profile, presents itself an attractive option between the classical Protestantism and Afro-Brazilian services and the popular Brazilian religiosity. This hypothesis was tested with the main focus the Universal Church of the Kingdom of God. For that, it was worked with reference researchers job on the topic, with literature produced by some leaders of this movement and with videographic material available on internet containing neo-pentecostal speeches and practices relevant to this study. From this effort, it was considered that the Neo-pentecostalism is a middle way between the Protestant tradition and the African and popular Brazilian religiosity, with notable ruptures in relation to its origin as well as many continuities; what makes this movement the expression of Protestantism that most suited the Brazilian reality.